2010
DOI: 10.1007/s00339-010-5874-y
|View full text |Cite
|
Sign up to set email alerts
|

Laser studies of metallic artworks

Abstract: Museum curators and archaeologists use analytical science to provide important information on artworks and objects. For example, scientific techniques provide information on artwork elemental composition, origin and authenticity, and corrosion products, while also finding use in the day-to-day conservation of many historical objects in museums and archaeological sites around the world. In this work two special cases are being discussed. In the first part of our work, physicochemical studies of an icon on a met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…All these experiments indicated that the 1064 nm laser pulse succeeded to clean metal coins; the only drawback comes from photothermal effects, which could be avoided only with the use of low fluences. This is also demonstrated in the literature [12][13][14][15].…”
Section: Materials and Laser Cleaningsupporting
confidence: 78%
“…All these experiments indicated that the 1064 nm laser pulse succeeded to clean metal coins; the only drawback comes from photothermal effects, which could be avoided only with the use of low fluences. This is also demonstrated in the literature [12][13][14][15].…”
Section: Materials and Laser Cleaningsupporting
confidence: 78%
“…Equation (1) represents the method to simulate the removed depth analytically. Lasers can remove unwanted layers that conventional techniques cannot remove safely [5]. Ahn et al showed that a near-infrared (NIR) laser pulse provides an effective tool for removing lubricants from carbon steel surfaces [6].…”
Section: Introductionmentioning
confidence: 99%
“…Konarski and Opalinska used SIMS and Fourier transform-infra-red (FT-IR) to study cold plasma cleaning of copper and aluminium. 39 Two lasers were compared for the cleaning process; a Q-switched Nd:YAG laser operating at 1064 nm and with a pulse duration of 6 ns and a GaAlAs diode laser operating at 780 nm and with a 90 ps laser pulse. The efficiency of the cleaning process was monitored using FT-IR.…”
Section: Non-ferrous Metals and Alloysmentioning
confidence: 99%